Dynamics of soil characteristics in eight-years old agri-horti-silviculture model in Bundelkhand region of Central India - Prasad, Rajendra; Singh, Ramesh; Handa, A.K.; Alam, B.; Shukla, Ashok; Singh, Prashant; Tripathi, V.D.; Kumar, Dhiraj; Kumar, Anil; Prasad, Niranjan (Indian Journal of Agroforestry, 2019)
The basic tenet of agroforestry is its ability to restore fertility of poor soil and the researchers always try to assess how different nutrients present in the soil respond to the presence of woody perennials amidst growing agri-crops.Hence, the present study was aimed to assess the effect of different woody plant species [Acacia senegal (L.) Willd. (kumat), Aegle marmelos (L.) Correa (bael), Citrus limon (L.) Osbeck (lemon), and Carissa carandas L. (karonda)], distance from their bases (0.5, 1.0, 2.0, 4.0 and 6.0 m) and depth (0-15 and 16-30 cm) on various soil characteristics [pH, electrical conductivity (EC), organic carbon (OC), available macro- and micro-nutrients) in a well established eight-years old agri-horti-silviculture model. The findings revealed that different plant species exhibited variable effects on studied soil parameters. Maximum OC, nitrogen (N), phosphorus (P) and iron (Fe) were recorded under A. senegal; EC, potassium (K) and manganese (Mn) under C. limon; and copper (Cu) and zinc (Zn) under C. carandas. Distance significantly affected most of the parameters. The pH, EC, OC, N, P, K and Zn were found higher near woody plant base and reduced gradually with increase in distance. Thus, the results of present study showed that among plant species, A. senegal can be more beneficial than other tested plant species, as it enhanced the status of essential nutrients (N, P and K) which improves soil health.